Perencanaan Struktur Gedung Hotel 5 Lantai di Desa Linggajati Kecamatan Cilimus Kabupaten Kuningan - Dewi, Alya Tri Puspita (Jurnal Civil Engineering Study, 2022)
Structural Planning of the 5-storey Hotel Building is located in Linggajati Village, Cilimus District, Kuningan Regency, the planned building area is 900 m2 and has 5 floors. Based on the results of the Con Penetration Test, it is known that the building was built on land with moderate soil conditions and based on its function is included in the risk category II, so this building was built using the SRPMK (Special Moment Resistant Frame System) method. The planning of the building refers to the building construction regulations in Indonesia. The method used in this planning earthquake analysis is the static equivalent analysis method based on SNI 1726:2019 concerning Procedures for Planning for Earthquake Resistance for Building and Non-Building Structures. The structure used for this building is reinforced concrete which refers to SNI 2847:2019 concerning Structural Concrete Requirements for buildings, SNI 1727:2020 concerning minimum loads for Building and Structural Design, for structural analysis the ETABS v.18.1.1 program is used. Control the need for reinforcement in the column using the SPCOlumn program